NURSING CARE FOR CLIENTS WHO EXPERIENCE POST OPERATING FEMUR FRACTURES WITH ACUTE PAIN NURSING PROBLEMS IN THE BIMA ROOM, JOMBANG HOSPITAL - Dwi Ayu Ningsih; Arif Wijaya; Ika Puspita Sari; Faisol Roni; Achmad Wahdi (Journal for Quality in Women's Health, 2023)
Background:Fracture is a break or damage to the continuity of bone tissue caused by an external pressure that is greater than can be absorbed by the bone. Method:The research design was a case study using 2 postoperative femur fracture clients as subjects with acute pain nursing problems, nursing care was carried out for 3 consecutive days using cold compress therapy. Result:The results of the study showed acute pain by administering cold compress therapy, the problem was resolved by reducing pain scale to mild pain scale. Analysis:The results of the evaluation carried out by the researchers during the three days of treatment on both clients with postoperative femoral fracture problems found the diagnosis of acute pain was resolved. Conclusion:Non-pharmacological management of postoperative fracture patients with pain is to use cold compress therapy. Giving cold compresses can reduce pain, increase the release of endorphins which block the transmission of painful stimuli.